Learning Management System as Support for the Independent Curriculum at SMK NU Sudirman Rogojampi: Learning Management System Sebagai Pendukung Kurikulum Merdeka di SMK NU Sudirman Rogojampi - Lukman Hakim; Arum Andary Ratry; Ika Yuniwati; Rafli Ainun Prasetya (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
SMK NU Sudirman Rogojampi is currently preparing to implement the Merdeka Curriculum in accordance with the Ministry of Education, Culture, Research, and Technology Regulation No. 12 of 2024. The Kurikulum Merdeka provides students with the freedom to explore their skills and interests. However, SMK NU Sudirman is currently lacking the necessary capacity, both in terms of infrastructure and human resources, to fully implement the curriculum. The learning system at SMK NU Sudirman Rogojampi remains conventional, relying on face-to-face classroom instruction. Additionally, the teachers at SMK NU Sudirman have not yet acquired the skills needed to develop digital learning media. Teaching materials are still based on textbooks and worksheets, which results in monotonous learning experiences and reduces student interest in learning. To address these challenges, this community service initiative proposes the development of a Learning Management System (LMS) and training on creating interactive learning media using H5P. Once the LMS is developed, teachers and students will be introduced to its usage. Additionally, interactive learning media creation workshops will be held for teachers, enabling them to deliver more engaging and enjoyable lessons for their students. The outcomes of this project indicate that both teachers and students were able to easily use the LMS. Furthermore, teachers found it easy to create interactive learning media. Students also showed greater interest in learning through the interactive media created by their teachers compared to conventional textbook